1999
DOI: 10.1046/j.1526-0976.1999.08094.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Biopsy-Confirmed Cervical Intraepithelial Neoplasia Grade 1: Colposcopic, Cytological, and Virological Risk Factors for Progression

Abstract: A total of 237 patients were evaluated as possible participants. The 74 exclusions at enrollment included 33 patients who had an entry diagnosis of CIN2 to CIN3 or who had lesions that were otherwise already unsafe to follow up, 39 who did not have a lesion on colposcopically directed biopsy, and 2 who were immediately noncompliant. Among the remaining 163 participants, the overall progression rate to histologically confirmed CIN3 was 8%, the persistence rate was 49%, and the regression rate was 43%. All progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This resulted in 125 studies being excluded. The remaining 89 studies were included for meta-analysis, of which 63 studies with CIN 1 patients, 8–70 42 studies with CIN 2 patients, 11,26,27,35–37,39,41–44,50,52,53,57,69–95 and 7 studies with CIN 3 patients 3,26,41,72,81,83,88 . The characteristics and the follow-up protocol of the included studies are summarized in Supplementary Tables 1–3, http://links.lww.com/LGT/A239, http://links.lww.com/LGT/A240, http://links.lww.com/LGT/A241.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in 125 studies being excluded. The remaining 89 studies were included for meta-analysis, of which 63 studies with CIN 1 patients, 8–70 42 studies with CIN 2 patients, 11,26,27,35–37,39,41–44,50,52,53,57,69–95 and 7 studies with CIN 3 patients 3,26,41,72,81,83,88 . The characteristics and the follow-up protocol of the included studies are summarized in Supplementary Tables 1–3, http://links.lww.com/LGT/A239, http://links.lww.com/LGT/A240, http://links.lww.com/LGT/A241.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, treatment of persistent CIN1 was believed to prevent progression to CIN2 and CIN3. However, subsequent research showed that CIN1 can be caused by many genotypes of HPV, that repeated CIN1 is not necessarily indicative of viral persistence, and that only 8% progress to CIN3 over 2 years, making treatment unnecessary in most patients …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was suggested that cervical inflammation may be a cofactor for high-grade cervical lesions in women infected with oncogenic HPV [15]. Similarly, two studies reported that genital infections leading to chronic inflammation increased the risk of developing CIN [42,43]. In all these studies, it was evident that inflammation was strongly related with CIN, a precursor lesion for development of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore the influence of different degrees of inflammation in the ASC, LSIL and HSIL, we analyzed the percentage of mild inflammation, moderate inflammation and severe inflammation in control group, ASC group, LSIL group and HSIL group. The result indicated that in the control group and the ASC group, the percentages of severe inflammation (2%, 19.46%) were lower than those with mild (42.5%, 43.8%) and moderate inflammation(15.8%, 25.58%). While, in the LSIL and HSIL groups, the percentages of severe inflammation (43.35%, 50.22%) were higher than mild(20.80%, 13.68%)and…”
Section: The Correlation Between Cervical Inflammation Degrees and Cymentioning
confidence: 90%